A Health-related quality of life and activities of daily living of Thai elderly people in Pathumthani Social Welfare Development Center for Older Persons - Khemmapak Charoensuksiri (Journal of Associated Medical Sciences, 2017)
Background: Currently, Thailand is an ageing society. An increase of age related to changes of physical and physiology. These changes lead to body degradation that affects a health-related quality of life and activities of daily living.